EFFECT OF STRAIN RATE ON MICROSTRUCTURE OF A LOW CARBON STEEL WIRE (Sciences & Technology. A, exactes sciences, 2010)
The commercial importance of low alloy carbon steels is due to their plastic deformation properties. These properties allow   them to be formed into useful shapes such as wires.  The present steel is produced by Trifisoud- Setif –Algeria and used for wiring. It is a low carbon steel wire containing mainly (weight %) 0.05%C, 0.3%Mn, 0.1%S and 0.12%Cr and is supplied as rods. The optical microscopic and SEM analyses are used to identify the microstructure of the material in as received and deformed conditions. It is found that tensile properties depend on the wiredrawing area reduction (tw). The annealing temperatures and the grain size are determined; they also vary with tw .